Feasibility Analysis of Company Investment in the Furniture Industry in Braja Selebah District, East Lampung - Lely Ayu Putri Mahmudah; Emi Maimunah (Lafadz Jaya Publisher, 2024)
This research aims to determine the feasibility of business investment in the Braja Selebah sub-district, East Lampung. This research uses data analysis carried out quantitatively and qualitatively. Quantitative data analysis is used to measure the feasibility of investment from a financial perspective using the business feasibility criteria analysis method. Analysis of business feasibility criteria is carried out using several methods, namely Net Present Value (NPV), Net Benefit/Cost (Net B/C), Gross B/C Ratio, Internal Rate of Return (IRR) and Payback Period, BEP, B/C Ratio , ROI. The results of this research indicate that the furniture industry business in Braja Selebah District is worthy of development. With a B/C RATIO value of 1.12, ROI was 12.61%, BEP in terms of quantity was 531, and BEP in terms of price was IDR 1,403,778/unit. NPV is IDR 73,065,902, Net B/C is 3.3, Gross B/c is 1.1, IRR is 30.57%, Payback Period is 18.78. Thus, it can be concluded that the furniture industry business in Braja Selebah sub-district is worthy of development.